Lithium secondary battery inculding cathode additives
Patent Information
- Application Number
- KR1020210070875
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-01
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2041-06-01
Smart Images

Figure 112021063310774-PAT00001
Abstract
Description
Technology Field
[0001] The present invention relates to a lithium secondary battery containing an anode additive, and more specifically, to a lithium secondary battery containing an anode additive in an anode composite layer. Background Technology
[0003] Recently, the demand for rechargeable batteries as an energy source has been increasing rapidly. Among these rechargeable batteries, lithium-ion batteries, which possess high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] Although graphite is primarily used as a negative electrode material for lithium secondary batteries, it is difficult to increase the capacity of lithium secondary batteries because graphite has a low capacity of 372 mAh / g per unit mass. Accordingly, to increase the capacity of lithium secondary batteries, negative electrode materials that form intermetallic compounds with lithium, such as silicon, tin, and their oxides, are being developed and used as non-carbon negative electrode materials that have a higher energy density than graphite. However, these non-carbon negative electrode materials have a problem in that, although they have a large capacity, their initial efficiency is low, resulting in high lithium consumption during initial charge-discharge and large irreversible capacity loss.
[0005] In this regard, a method has been proposed to overcome irreversible capacity loss of the anode by using a material that can provide a lithium ion source or storage to the cathode material and exhibits electrochemical activity after the first cycle so as not to degrade the overall performance of the battery. Specifically, a method is known in which an oxide containing an excess amount of lithium, such as Li6CoO4, is applied to the cathode as a sacrificial cathode material or an irreversible additive (or over-discharge inhibitor).
[0006] Meanwhile, conventional irreversible additives such as the above Li6CoO4 are generally manufactured by reacting cobalt oxide, etc., with an excess amount of lithium oxide. The irreversible additive manufactured in this way is structurally unstable and generates a large amount of oxygen gas (O2) as charging proceeds. If the irreversible additive does not fully react and remains during the initial charging of the secondary battery, that is, during the activation of the battery, it may cause a reaction during the subsequent charging and discharging process, thereby generating side reactions or a large amount of oxygen gas inside the battery. The oxygen gas generated in this way can cause volume expansion of the electrode assembly, and thus act as one of the main factors causing a decrease in battery performance.
[0007]
[0008] In addition, conventionally used irreversible additives are nearly insulators due to their 2D percolating network, ~10 -11 It exhibits a very low electrical conductivity of S / cm. This low electrical conductivity increases the electrical resistance of the anode. In this case, it exhibits a large capacity of over 200 mAh / g at low C-rates, but as the C-rate increases, the performance decreases rapidly as charging and discharging proceeds due to the high resistance, so the charge and discharge capacity of the battery decreases, and there is a limitation that high-speed charging and discharging is difficult.
[0009] Therefore, there is a need for the development of lithium secondary batteries that not only have excellent electrical performance but also improved safety. Prior art literature
[0011] Republic of Korea Published Patent Application No. 10-2019-0064423 The problem to be solved
[0012] Accordingly, the objective of the present invention is to provide a lithium secondary battery with excellent electrical performance and improved safety. means of solving the problem
[0014] In order to solve the aforementioned problem,
[0015] In one embodiment of the present invention,
[0016] A lithium secondary battery comprising: an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes; and an electrolyte.
[0017] The above anode comprises an anode current collector and an anode composite layer located on the anode current collector, comprising an anode active material, an anode additive represented by the following chemical formula 1, a conductive material, and a binder.
[0018] The above lithium secondary battery provides a lithium secondary battery that satisfies the following Equation 1 with a value of 2.0 or higher after charging to 100% SOC in an activation process under conditions of a voltage of 3.5 to 4.5 V and a current of 0.1 to 0.5 C:
[0019] [Chemical Formula 1]
[0020] Li p Co (1-q) M 1 q O4
[0021] In the above chemical formula 1,
[0022] M 1 It is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0023] p and q are 5≤p≤7 and 0≤q≤0.5, respectively;
[0024] [Equation 1]
[0025] A LCO / A0
[0026] In Equation 1,
[0027] A LCOrepresents the amount of carbon monoxide (CO) and carbon dioxide (CO2) gas generated (ml) when the anode contains an anode additive represented by Chemical Formula 1, and
[0028] A0 represents the amount of carbon monoxide (CO) and carbon dioxide (CO2) gas generated (ml) when the anode does not contain the anode additive represented by Chemical Formula 1.
[0029] Specifically, the above lithium secondary battery can satisfy Equation 1 at 3.0 or higher.
[0031] In addition, the present invention provides a lithium secondary battery satisfying the following formula 2 at 0.8 or less:
[0032] [Equation 2]
[0033] B LCO / B0
[0034] In Equation 2,
[0035] B LCO represents the amount of gas generated (ml) of propene (C3H6) and propane (C3H8) when the anode contains an anode additive represented by Chemical Formula 1, and
[0036] B0 represents the amount of gas produced (ml) of propene (C3H6) and propane (C3H8) when the anode does not contain the anode additive represented by Chemical Formula 1.
[0037] Meanwhile, in the present invention, the anode additive may have a tetragonal structure with a space group of P42 / nmc.
[0038] In addition, the content of the anode additive may be 0.1 to 5 parts by weight per 100 parts by weight of the anode composite layer.
[0039] In addition, the above-mentioned positive electrode active material may be a lithium metal composite oxide represented by the following chemical formula 2:
[0040] [Chemical Formula 2]
[0041] Li x [Ni y Coz Mn w M 2 v ]O u
[0042] In the above chemical formula 2,
[0043] M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0044] x, y, z, w, v, and u are 1.0≤x≤1.30, 0.1≤y<0.95, and 0.01, respectively. <z≤0.5, 0.01<w≤0.5, 0≤v≤0.2, 1.5≤u≤4.5이다.
[0045] In addition, the conductive material may include one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Denka black, Ketjen black, Super-P, Channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.
[0046] In addition, the conductive material may be included in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the anode composite layer.
[0047] Furthermore, in the lithium secondary battery according to the present invention, the negative electrode comprises a negative electrode current collector and a negative electrode composite layer located on the negative electrode current collector and containing a negative electrode active material. In addition, the negative electrode active material may contain a carbon material and a silicon material.
[0048] In addition, the above silicon material comprises silicon (Si) particles and silicon oxide (SiO₂). X It may include one or more of the particles (1≤X≤2), and the silicon material may be included in an amount of 1 to 20 parts by weight in 100 parts by weight of the cathode composite layer.
[0050] In addition, in one embodiment of the present invention,
[0051] A method for activating a lithium secondary battery is provided, comprising the process of charging the lithium secondary battery to an SOC of 10% to 100% under conditions of a voltage of 3.5 to 4.5 V and a current of 0.1 to 0.5 C. Effects of the invention
[0053] In the lithium secondary battery according to the present invention, the positive electrode is manufactured by including a positive electrode additive represented by Formula 1 as an irreversible additive in the positive electrode composite layer, and by controlling the ratio of carbon monoxide and carbon dioxide generated during the activation process to satisfy a specific range depending on whether the positive electrode additive is used, the content of hydrogen and hydrocarbons relative to the total amount of gas generated during the activation process can be reduced. Accordingly, the present invention has the advantage of not only improving the safety of the lithium secondary battery but also improving the charge-discharge efficiency of the lithium secondary battery. Specific details for implementing the invention
[0055] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are to be described in detail in the detailed description.
[0056] However, this is not intended to limit the invention to specific embodiments, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.
[0057] In the present invention, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0058] Furthermore, in the present invention, when a part such as a layer, film, region, or plate is described as being "on" another part, this includes not only cases where it is "immediately above" the other part, but also cases where there is another part in between. Conversely, when a part such as a layer, film, region, or plate is described as being "under" another part, this includes not only cases where it is "immediately below" the other part, but also cases where there is another part in between. Additionally, in the present application, being "placed on" may include cases where it is placed on the lower part as well as on the upper part.
[0059] In addition, in the present invention, "main component" may mean 50% or more by weight, 60% or more by weight, 70% or more by weight, 80% or more by weight, 90% or more by weight, 95% or more by weight, or 97.5% or more by weight with respect to the total weight of the composition or specific component, and in some cases, may mean 100% by weight when constituting the entire composition or specific component.
[0060] In addition, in the present invention, "Ah" is a unit of capacity for a lithium secondary battery, referred to as "ampere-hour," and signifies the amount of current per hour. For example, if the battery capacity is "3000 mAh," it means that it can be discharged for one hour with a current of 3000 mA.
[0062] The present invention will be described in more detail below.
[0064] lithium secondary battery
[0065] In one embodiment of the present invention,
[0066] anode;
[0067] cathode;
[0068] An electrode assembly comprising a separator disposed between an anode and a cathode; and
[0069] A lithium secondary battery containing an electrolyte is provided.
[0071] At this time, the anode comprises an anode current collector and an anode composite layer prepared by applying, drying, and pressing an anode slurry onto the anode current collector, and the anode composite layer has a composition containing an anode active material, an anode additive, a conductive material, and a binder.
[0072] In a specific example, the anode additive may be lithium cobalt oxide represented by the following chemical formula 1:
[0073] [Chemical Formula 1]
[0074] Li p Co (1-q) M 1 q O4
[0075] In the above chemical formula 1,
[0076] M 1 It is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0077] p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0078] The above-mentioned cathode additive contains an excess amount of lithium, which can provide lithium for lithium consumption caused by irreversible chemical and physical reactions at the anode during initial charging, thereby increasing the charge capacity of the battery and reducing irreversible capacity, which can improve lifespan characteristics.
[0079] Among these, the cathode additive represented by Chemical Formula 1 above has a higher lithium ion content compared to nickel-containing oxides commonly used in the industry. Since this allows for the replenishment of lithium ions lost due to irreversible reactions during the initial activation of the battery, the charge and discharge capacity of the battery can be significantly improved. Furthermore, compared to iron and / or manganese-containing oxides commonly used in the industry, it has the advantage of excellent battery stability as there are no side reactions caused by the leaching of transition metals during battery charging and discharging. Examples of such lithium metal oxides represented by Chemical Formula 1 include Li6CoO4 and Li6Co 0.5 Zn 0.5 O4, Li6Co 0.7 Zn 0.3 It may include O4, etc.
[0080] In addition, the anode additive represented by the above chemical formula 1 may have a tetragonal crystal structure, and among these, may be included in the space group of P42 / nmc having a twisted tetrahedral structure formed by cobalt and oxygen elements.
[0081] In addition, the above-mentioned anode additive may be included in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the anode composite layer, and specifically, may be included in an amount of 0.1 to 5 parts by weight; 0.1 to 4.5 parts by weight; 0.3 to 4 parts by weight; 0.3 to 3.5 parts by weight; 0.5 to 3 parts by weight; 0.5 to 2.5 parts by weight; 0.7 to 2 parts by weight; or 0.7 to 1.8 parts by weight per 100 parts by weight of the anode composite layer. By controlling the content of the anode additive to the above range, the present invention can prevent a decrease in charge / discharge capacity due to insufficient replenishment of lithium ions lost by irreversible reactions caused by a low content of the anode additive, and can prevent a large amount of oxygen gas from being generated during the charge / discharge of the battery due to an excessive amount of anode additive.
[0082] Furthermore, the above lithium secondary battery contains a positive additive represented by Chemical Formula 1, thereby controlling the ratio of carbon monoxide and carbon dioxide generated during the activation process to satisfy a specific range, which can improve the safety of the battery and achieve excellent performance during charging and discharging.
[0083] Specifically, conventionally used irreversible additives have a problem of generating a large amount of gas as charging proceeds due to structural instability. However, in the lithium secondary battery of the present invention, even though the positive electrode contains a positive electrode additive represented by Chemical Formula 1 in the positive electrode composite layer, the ratio of hydrogen and hydrocarbon content to the total amount of gas generated during the activation process can be reduced. Accordingly, the safety of the battery can be improved, and excellent performance can be achieved during charging and discharging.
[0084] In one example, after charging to 100% SOC in an activation process under conditions of a voltage of 3.5 to 4.5 V and a current of 0.1 to 0.5 C, the ratio (A) of the amount of carbon monoxide (CO) and carbon dioxide (CO2) generated by a lithium secondary battery containing a positive electrode additive represented by Formula 1 and the amount of carbon monoxide (CO) and carbon dioxide (CO2) generated by a lithium secondary battery not containing a positive electrode additive LCO The following formula 1 representing / A0) can be satisfied at 2.0 or higher. Specifically, it can be satisfied as 2.5 or higher, 3.0 or higher, 3.2 or higher, 3.5 or higher, 2.5 to 20; 3.0 to 18; 3.2 to 16; or 3.5 to 15:
[0085] [Equation 1]
[0086] A LCO / A0
[0087] In Equation 1,
[0088] A LCOrepresents the amount of carbon monoxide and carbon dioxide gas generated (ml / Ah) when the anode contains an anode additive represented by Chemical Formula 1, and
[0089] A0 represents the amount of carbon monoxide and carbon dioxide gas generated (ml / Ah) when the anode does not contain the anode additive represented by Chemical Formula 1.
[0091] In another example, in the lithium secondary battery according to the present invention, after charging to 100% SOC in the activation process, the ratio (B) of the amount of gas generated of propene (C3H6) and propane (C3H8) of a lithium secondary battery containing a positive electrode additive represented by Formula 1 and the amount of gas generated of propene (C3H6) and propane (C3H8) of a lithium secondary battery not containing a positive electrode additive represented by Formula 1 LCO The following formula 2, representing / B0), can be satisfied as 0.8 or less. Specifically, it can be satisfied as 0.75 or less, 0.70 or less, 0.68 or less, 0.20 to 0.75; 0.30 to 0.70; or 0.40 to 0.68.
[0092] [Equation 2]
[0093] B LCO / B0
[0094] In Equation 2,
[0095] B LCO represents the gas generation amount (ml / Ah) of propene (C3H6) and propane (C3H8) when the anode contains an anode additive represented by Chemical Formula 1, and
[0096] B0 represents the gas generation amount (ml / Ah) of propene (C3H6) and propane (C3H8) when the anode does not contain the anode additive represented by Chemical Formula 1.
[0097] That is, in the lithium secondary battery according to the present invention, after charging to 100% SOC in the activation process, if it contains a positive additive represented by Chemical Formula 1, the total amount of gas generated may increase, but the content of hydrogen and hydrocarbons relative to the total amount of gas generated can be reduced by controlling the ratio of carbon monoxide and carbon dioxide as described above.
[0098] Meanwhile, in the present invention, the amount of gas generated refers to the amount of gas generated (ml) relative to the capacity (Ah) of each battery cell.
[0100] The above-mentioned cathode active material is a cathode active material capable of reversible intercalation and deintercalation, and may include a lithium metal composite oxide represented by the following chemical formula 2 as a main component:
[0101] [Chemical Formula 2]
[0102] Li x [Ni y Co z Mn w M 2 v ]O u
[0103] In the above chemical formula 2,
[0104] M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and
[0105] x, y, z, w, v, and u are 1.0≤x≤1.30, 0.1≤y<0.95, and 0.01, respectively. <z≤0.5, 0.01<w≤0.5, 0≤v≤0.2, 1.5≤u≤4.5이다.
[0106] The lithium metal composite oxide represented by the above chemical formula 2 is a composite metal oxide containing lithium and nickel, wherein LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.8 Co0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 It may include one or more compounds selected from the group consisting of O2.
[0107] In addition, the content of the above-mentioned positive active material may be 85 to 95 parts by weight per 100 parts by weight of the positive composite layer, and specifically, may be 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight.
[0108] In addition, the conductive material is used to improve the electrical performance of the anode, and while commonly used in the industry may be applied, specifically, it may include one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Denka black, Ketjen black, Super-P, Channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.
[0109] As an example, the conductive material may use carbon black or Denka black alone or in combination.
[0110] In addition, the conductive material may be included in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the anode composite layer, and specifically, may be included in an amount of 0.1 to 4 parts by weight; 2 to 4 parts by weight; 1.5 to 5 parts by weight; 1 to 3 parts by weight; 0.1 to 2 parts by weight; or 0.1 to 1 part by weight.
[0111] In addition, the binder serves to bind the cathode active material, cathode additive, and conductive material together, and any binder having this function can be used without particular limitation. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidenefluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidenefluoride (PVdF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As one example, the binder may include polyvinylidenefluoride.
[0112] In addition, the binder may be included in an amount of 1 to 10 parts by weight per 100 parts by weight of the composite layer, specifically 2 to 8 parts by weight; or 1 to 5 parts by weight of a conductive material.
[0113] In addition, the average thickness of the above composite layer is not particularly limited, but specifically may be 50㎛ to 300㎛, and more specifically may be 100㎛ to 200㎛; 80㎛ to 150㎛; 120㎛ to 170㎛; 150㎛ to 300㎛; 200㎛ to 300㎛; or 150㎛ to 190㎛.
[0114] In addition, the anode may be used as an anode current collector that has high conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, surface-treated materials such as carbon, nickel, titanium, silver, etc. may be used. Furthermore, the anode current collector may have fine irregularities formed on its surface to increase the adhesion of the anode active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics are possible. Moreover, the average thickness of the current collector may be appropriately applied in the range of 3 to 500 μm, taking into consideration the conductivity and total thickness of the manufactured anode.
[0116] In addition, the negative electrode of the lithium secondary battery according to the present invention is manufactured by coating, drying, and pressing a negative electrode active material onto a negative electrode current collector, and, if necessary, a conductive material, an organic binder polymer, an additive, etc., as in the positive electrode may be optionally further included.
[0117] In addition, the above-mentioned cathode active material may include, for example, a carbon material and a silicon material. The above-mentioned carbon material refers to a carbon material having carbon atoms as its main component. Such carbon materials may include graphite, which has a completely layered crystal structure like natural graphite; soft carbon having a low-crystallinity layered crystal structure (graphene structure; a structure in which hexagonal honeycomb-shaped planes of carbon are arranged in layers); hard carbon in which such structures are mixed with amorphous portions; artificial graphite; expanded graphite; carbon fiber; non-graphitized carbon; carbon black; acetylene black; ketjen black; carbon nanotubes; fullerene; activated carbon; graphene; carbon nanotubes; and, preferably, one or more selected from the group consisting of natural graphite, artificial graphite, graphene, and carbon nanotubes. More preferably, the above-mentioned carbon material may include natural graphite and / or artificial graphite, and together with the natural graphite and / or artificial graphite, may include one or more of graphene and carbon nanotubes. In this case, the carbon material may comprise 0.1 to 10 parts by weight of graphene and / or carbon nanotubes per 100 parts by weight of the total carbon material, and more specifically, may comprise 0.1 to 5 parts by weight or 0.1 to 2 parts by weight of graphene and / or carbon nanotubes per 100 parts by weight of the total carbon material.
[0118] In addition, the above silicon material is a particle containing silicon (Si) as a main component as a metallic component, comprising silicon (Si) particles and silicon oxide (SiO₂). X It may include one or more of the particles (1≤X≤2). As one example, the silicon material may include silicon (Si) particles, silicon monoxide (SiO) particles, silicon dioxide (SiO2) particles, or a mixture of these particles.
[0119] In addition, the silicon material may have a form in which crystalline particles and amorphous particles are mixed, and the ratio of the amorphous particles may be 50 to 100 parts by weight, specifically 50 to 90 parts by weight; 60 to 80 parts by weight; or 85 to 100 parts by weight, based on 100 parts by weight of the total silicon material. By controlling the ratio of amorphous particles contained in the silicon material to the above range, the present invention can improve thermal stability and flexibility without degrading the electrical properties of the electrode.
[0120] In addition, the silicon material may include a carbon material and a silicon material, and may be included in an amount of 1 to 20 parts by weight per 100 parts by weight of the cathode composite layer, and specifically, may be included in an amount of 5 to 20 parts by weight; 3 to 10 parts by weight; 8 to 15 parts by weight; 13 to 18 parts by weight; or 2 to 7 parts by weight per 100 parts by weight of the cathode composite layer.
[0121] The present invention can improve the charging capacity per unit mass while reducing lithium consumption and irreversible capacity loss during the initial charging and discharging of the battery by controlling the content of carbon material and silicon material included in the negative electrode active material to the range described above.
[0122] As one example, the negative electrode active material may comprise 95 ± 2 parts by weight of graphite and 5 ± 2 parts by weight of a mixture of silicon monoxide (SiO) particles and silicon dioxide (SiO2) particles uniformly mixed, based on 100 parts by weight of the negative electrode composite layer. By controlling the content of carbon material and silicon material included in the negative electrode active material to the above range, the present invention can improve the charge capacity per unit mass while reducing lithium consumption and irreversible capacity loss during the initial charge and discharge of the battery.
[0123] In addition, the cathode composite layer may have an average thickness of 100㎛ to 200㎛, and specifically, may have an average thickness of 100㎛ to 180㎛, 100㎛ to 150㎛, 120㎛ to 200㎛, 140㎛ to 200㎛, or 140㎛ to 160㎛.
[0124] In addition, the above-mentioned negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. may be used, and in the case of copper or stainless steel, surface-treated carbon, nickel, titanium, silver, etc. may be used. Furthermore, similar to the positive electrode current collector, the above-mentioned negative electrode current collector may form fine irregularities on its surface to strengthen the bonding force with the negative electrode active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics are possible. In addition, the average thickness of the above-mentioned negative electrode current collector may be appropriately applied in the range of 3 to 500 μm, taking into consideration the conductivity and total thickness of the manufactured negative electrode.
[0125] In addition, the separator is interposed between the anode and the cathode, and an insulating thin film having high ion permeability and mechanical strength is used. The separator is not particularly limited as long as it is commonly used in the industry, but specifically, a sheet or nonwoven fabric made of chemically resistant and hydrophobic polypropylene; glass fiber; or polyethylene may be used, and in some cases, a composite separator in which inorganic particles / organic particles are coated by an organic binder polymer on a porous polymer substrate such as the sheet or nonwoven fabric may be used. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte may also serve as the separator. Furthermore, the pore diameter of the separator may be an average of 0.01 to 10 μm, and the thickness may be an average of 5 to 300 μm.
[0126] Meanwhile, the above positive and negative electrodes may be wound into a jelly roll form and stored in a cylindrical battery, a prismatic battery, or a pouch-type battery, or stored in a pouch-type battery in a folding or stack-and-folding form, but are not limited thereto.
[0127] In addition, the lithium salt-containing electrolyte according to the present invention may consist of an electrolyte and a lithium salt, and the electrolyte may be a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, etc.
[0128] As the above-mentioned non-aqueous organic solvent, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfranc, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolone, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolone derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, etc. may be used.
[0129] The above organic solid electrolyte may be, for example, a polyethylene derivative, a polyethylene oxide derivative, a polypropylene oxide derivative, a phosphate ester polymer, agitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, a polymer containing an ionic dissociator, etc.
[0130] As the above-mentioned inorganic solid electrolyte, for example, nitrides, halides, sulfates of Li such as Li3N, LiI, Li5Ni2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2, etc., may be used.
[0131] The above lithium salt is a substance that dissolves well in a non-aqueous electrolyte, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB10Cl 10 LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylboronicate, imide, etc. may be used.
[0132] In addition, for the purpose of improving charge / discharge characteristics and flame retardancy, the electrolyte may be further enriched with, for example, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, to impart non-flammability, halogen-containing solvents such as carbon tetrachloride and trifluoroethylene may be further enriched, carbon dioxide gas may be further enriched to improve high-temperature storage characteristics, and FEC (Fluoro-Ethylene Carbonate), PRS (Propene Sultone), etc.
[0134] Activation method for lithium secondary batteries
[0135] In one embodiment of the present invention,
[0136] A method for activating a lithium secondary battery is provided, comprising the process of charging the lithium secondary battery to an SOC of 10% to 100% under conditions of a voltage of 3.5 to 4.5 V and a current of 0.1 to 0.5 C.
[0137] When the first charge of a lithium secondary battery is performed, lithium ions originating from lithium transition metal oxides, such as the cathode active material and cathode additive contained in the cathode, move to the carbon electrode of the anode. Since these lithium ions are highly reactive, they react with the carbon anode to produce compounds such as Li2CO3, LiO, and LiOH, and an SEI film is formed on the surface of the anode by these compounds. The SEI film is an insulator that forms when the amount of ion movement in the battery increases. Once the SEI film is formed, it prevents lithium ions from reacting with other substances at the anode during subsequent secondary battery charging, and functions as a kind of ion tunnel to allow only lithium ions to pass through. Since lithium ions do not react with the anode or other substances once this SEI film is formed, the amount of lithium ions is reversibly maintained, and the charging and discharging of the secondary battery are maintained reversibly, thereby improving the lifespan of the secondary battery. Furthermore, because it does not easily collapse even when left at high temperatures or subjected to repeated charging and discharging, changes in the battery thickness occur less.
[0138] Accordingly, in the activation method according to the present invention, lithium ions derived from the positive electrode active material and / or positive electrode additive form a solid electrolyte interphase (SEI) film on the surface of the negative electrode, and by applying current to the lithium secondary battery to induce delithiation and decomposition of lithium ions of the positive electrode additive, the battery can be charged and at the same time, a gas derived from the positive electrode additive can be formed inside the battery.
[0139] In addition, the activation step may be performed under temperature conditions higher than room temperature to lower the resistance of the electrode. Specifically, the activation step may be performed under temperature conditions of 40°C to 70°C, and more specifically, under temperature conditions of 40°C to 60°C; 45°C to 60°C; 50°C to 65°C; 50°C to 60°C; or 52°C to 58°C. By performing each activation step under temperature conditions satisfying the above ranges, the present invention enables charging of the secondary battery under lower resistance conditions of the anode, thereby increasing the efficiency of the activation step and improving the uniformity of the SEI film formed in the first activation step.
[0140] In addition, the execution time of the above activation step may be performed for 1 minute to 100 minutes, and specifically, for 1 minute to 100 minutes; 1 minute to 60 minutes; 1 minute to 40 minutes; 10 minutes to 40 minutes; 20 minutes to 40 minutes; 10 minutes to 30 minutes; and 1 minute to 10 minutes.
[0141] Furthermore, a process of degassing the gas formed inside the lithium secondary battery after the activation step described above may be performed. In the lithium secondary battery after the activation step, a large amount of gas is generated inside due to the delithiation and / or decomposition of the cathode additive contained in the composite layer of the cathode; if this gas is not removed, it may cause swelling of the battery along with the gas. However, the present invention can prevent this by additionally degassing the lithium secondary battery after the activation step.
[0142] Here, the degassing can be performed by applying pressure to the outer surface of the lithium secondary battery using a pressurizing device such as a jig, and the pressure can be applied at 10 to 900 kgf / ㎠ for 4 to 6 seconds, but is not limited thereto.
[0143] At this time, the gas removed during degassing of the lithium secondary battery can satisfy Equation 1 at 2.0 or higher:
[0144] [Equation 1]
[0145] A LCO / A0
[0146] In Equation 1,
[0147] A LCO represents the amount of carbon monoxide (CO) and carbon dioxide (CO2) gas generated (ml / Ah) when the anode contains an anode additive represented by Chemical Formula 1, and
[0148] A0 represents the amount of carbon monoxide (CO) and carbon dioxide (CO2) gas generated (ml / Ah) when the anode does not contain the anode additive represented by Chemical Formula 1.
[0149] Furthermore, the method for activating a lithium secondary battery according to the present invention may further include an aging step for aging the activated lithium secondary battery after the third activation step. The aging step may allow the SEI film to be further stabilized and reformed to a uniform thickness by thermal energy and electrochemical energy. To this end, the aging step may be performed at 20 to 40°C, specifically 20 to 30°C; or at 20 to 25°C for 0.5 to 30 hours.
[0151] The present invention will be explained in more detail below through examples and experimental examples.
[0152] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0154] Example 1.
[0155] 1) Manufacturing of lithium secondary batteries
[0156] LiNi as a positive electrode active material 0.6 Co 0.2 Mn 0.1 Al 0.1A slurry for an anode composite layer was prepared by weighing 296 parts by weight of O2, 1 part by weight of Li6CoO4 as an anode additive, 2 parts by weight of PVdF as a binder, and 3 parts by weight of carbon black as a conductive material, and mixing them in an N-methylpyrrolidone (NMP) solvent (anode active material:anode additive = 99.15:0.85). The slurry for the anode composite layer was applied to an aluminum foil, dried, and then rolled to form an anode having an anode composite layer (average thickness: 130 μm).
[0157] As a cathode active material, a slurry for a cathode composite layer was prepared by mixing natural graphite, a carbon black conductive material, and a PVdF binder in a weight ratio of 85:10:5 in an N-methylpyrrolidone solvent, and the slurry was coated onto a copper foil to produce a cathode having a cathode composite layer (average thickness: 180 μm).
[0158] An electrode assembly was manufactured by laminating a separator (thickness: approximately 16 μm) made of porous polyethylene (PE) film between the manufactured positive and negative electrodes. After placing the electrode assembly inside a battery case, an electrolyte was injected into the case, and the assembly was left at room temperature for 3 days to allow sufficient impregnation of the electrolyte to produce a lithium secondary battery. At this time, the electrolyte was prepared by dissolving 1.0 M concentration lithium hexafluorophosphate (LiPF6) in an organic solvent composed of ethylene carbonate / dimethyl carbonate / ethylmethyl carbonate (the mixed volume of EC / DMC / EMC was 3 / 4 / 3).
[0160] 2) Activation of lithium secondary batteries
[0161] An activation step was performed on the manufactured lithium secondary battery. Specifically, the activation temperature was 55℃, and the lithium secondary battery was activated by charging it to 100% capacity (SOC) under conditions of a constant current of 0.2C and 4.3V. After charging, the gas inside the battery was degassed using a jig.
[0163] Examples 2–3 and Comparative Examples 1–3. Preparation and activation of lithium secondary batteries
[0164] A lithium secondary battery was manufactured using the same method as in Example 1, except that the content of the positive active material and the positive additive was changed during the manufacture of the lithium secondary battery.
[0165] Then, an activation step was performed on the manufactured lithium secondary battery.
[0167] The composition of the anodes prepared in the examples and comparative examples is shown in Table 1 below.
[0168] Composition (parts by weight) of slurry for anode manufacturing Cathode active material (LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2) Anode additive (Li6CoO4) (Cathode active material: Cathode additive) Binder (PVdF) Conductive agent (Carbon Black) Example 1 95.0 0.9 99.15:0.85 1.6 2.5 Example 2 94.3 1.6 98.5:1.5 1.6 2.5 Comparative Example 1 95.9 - 1.6 2.5 Comparative Example 2 95.6 0.3 99.7:0.3 1.6 2.5 Comparative Example 3 89.6 6.3 94:6 1.6 2.5
[0170] Experimental Example.
[0171] To evaluate the performance of the cathode for a lithium secondary battery according to the present invention, the following experiment was performed.
[0173] a. Analysis of the composition and content of gases generated during the activation process
[0174] The components and content of each gas generated internally during the formation process of the lithium secondary battery according to the examples and comparative examples were analyzed, and the results are shown in Table 2 below.
[0175] Unit (ml) Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Hydrogen (H2) 7.4 9.7 4.1 5.2 10.2 Carbon monoxide (CO) 7.2 18 3.2 5.0 25.8 carbon dioxide (CO2) 9.5 45 1.4 2.5 80.1 methane (CH4) 2.8 3.9 0.6 1.0 4.5 Acetylene (C2H2) 0 0 0 0 0 Ethene (C2H4) 36 44 28 32 46 Ethane (C2H6) 1.2 1.7 0.5 1.0 2.5 Propene (C3H6) 0.3 0.2 0.5 0.4 0.1 Propane (C3H8) 0 0 0 0 0 Total gas production (ml) 64.4 122.5 38.3 47.1 169.2 Cell capacity (Ah) 80.31 79.63 77.87 78.39 88.22 Gas generation rate per cell capacity (ml / Ah) 0.80 1.54 0.49 0.60 1.92
[0176] As shown in Table 2 above, lithium secondary batteries containing cathode additives had a higher gas generation rate compared to lithium secondary batteries without cathode additives. In particular, it can be seen that the gas generation rate (ml / Ah) relative to cell capacity is higher as the content of cathode additive increases.
[0178] The content of carbon monoxide and carbon dioxide generated internally during the formation process of the lithium secondary battery according to the examples and comparative examples was evaluated, and the results are shown in Table 3 below.
[0179] Unit (ml) Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Carbon monoxide (CO) 7.2 18 3.2 5.0 25.8 carbon dioxide (CO2) 9.5 45 1.4 2.5 80.1 Amount of hydrocarbon (CO & CO2) gas generated 16.7 63 4.6 7.5 105.9 Cell capacity (Ah) 80.31 79.63 77.87 78.39 80.22 CO and CO2 gas generation rate per cell capacity (ml / Ah) 0.21 0.79 0.06 0.09 1.32 TO LCO / A0 3.5 13.17 - 1.5 22.0
[0180] Referring to Table 3 above, lithium secondary batteries containing cathode additives produced higher amounts of carbon monoxide and carbon dioxide compared to lithium secondary batteries without cathode additives. In particular, it can be seen that the amount of carbon monoxide and carbon dioxide produced increases with increasing content of cathode additives.
[0181] The content of hydrogen and hydrocarbons, excluding carbon monoxide and carbon dioxide, among the gases generated during the activation process is shown in Table 4 below.
[0182] Unit (ml) Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Hydrogen (H2) 7.4 9.7 4.1 5.2 10.2 methane (CH4) 2.8 3.9 0.6 1.0 4.5 Ethen (C2H2) 0 0 0 0 0 Ethane (C2H4) 36 44 28 32 46 Ethane (C2H6) 1.2 1.7 0.5 1.0 2.5 Propene (C3H6) 0.3 0.2 0.5 0.4 0.1 Propane (C3H8) 0 0 0 0 0 Amount of hydrogen and hydrocarbon gas generated 47.7 59.5 33.7 39.6 63.3 Total gas generation 64.4 122.5 38.3 47.1 169.2 Gas generation amount of hydrogen and hydrocarbons relative to total gas generation amount 0.74 0.49 0.87 0.84 0.37
[0183] Referring to Table 4 above, it was confirmed that although the total amount of gas generated during the activation process increased depending on whether the anode additive was used, the ratio of hydrogen and hydrocarbons to the total amount of gas generated during the activation process was reduced by adjusting the ratio of carbon monoxide and carbon dioxide to satisfy a specific range. In particular, in Example 2, the amount of hydrogen and hydrocarbons to the total amount of gas generated was confirmed to be 0.49.
[0184] Lithium secondary batteries activated according to the conditions of the examples and comparative examples were A through gas component and content analysis. LCO It was confirmed that the / A0 value is 3.0 or higher.
[0185] Meanwhile, the activated lithium secondary battery of Comparative Example 3 had a total gas generation amount of 169.2 ml, which was too high and caused volume expansion of the electrode assembly, and it was determined that this would lead to a decrease in battery performance.
[0187] In addition, the content of propene and propane generated internally during the formation process of the lithium secondary battery according to the examples and comparative examples was evaluated, and the results are shown in Table 5 below.
[0188] Unit (ml) Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Propene (C3H6) 0.3 0.2 0.5 0.4 0.1 Propane (C3H8) 0 0 0 0 0 Gas generation amount of C3H6 and C3H8 0.3 0.2 0.5 0.4 0.1 Cell capacity (Ah) 80.31 79.63 77.87 78.39 80.22 Gas generation of C3H6 and C3H8 relative to cell capacity (ml / Ah) 0.004 0.003 0.006 0.005 0.001 B LCO / B0 0.67 0.5 - 0.83 0.16
[0189] Lithium secondary batteries activated according to the conditions of the examples and comparative examples were confirmed to satisfy the following Equation 3 at 0.8 or less through gas component and content analysis.
[0191] Cycle life performance evaluation
[0192] In the examples and comparative examples, the activated lithium secondary batteries were discharged to 2V (C-rate = 0.1C), and subsequently, the capacity retention rate (Capacity Retention [%]) was measured while performing 100 charge-discharge cycles (n=100) at 25°C under conditions of a charge termination voltage of 4.25V, a discharge termination voltage of 2.5V, and 0.5C / 0.5C. At this time, the capacity retention rate was calculated using Equation 1 below, and the results are shown in Table 6 below:
[0193] [Equation 1]
[0194] Capacity Retention Rate (%) = (Discharge capacity after n charge-discharge cycles / Discharge capacity after 1 charge-discharge cycle) × 100
[0195] Initial charge capacity [mAh / g] Capacity retention rate after 100 charge / discharge cycles [%] Example 1 712 98% Example 2 721 97% Comparative Example 1 709 89% Comparative Example 2 706 92% Comparative Example 3 692 94%
[0196] Referring to Table 6 above, it was confirmed that the lithium secondary batteries activated according to the example have an initial charge capacity of 710 mAh / g or more and a capacity retention rate of 97% or more after 100 charge-discharge cycles, whereas the lithium secondary batteries activated according to the comparative example have an initial charge capacity and a capacity retention rate after 100 charge-discharge cycles lower than the lithium secondary batteries of the example.
[0198] From these results, it was confirmed that in the lithium secondary battery according to the present invention, the amount of carbon monoxide and carbon dioxide generated is higher as the content of the cathode additive represented by Formula 1 as an irreversible additive in the cathode composite layer increases, but the content of hydrogen and hydrocarbons relative to the total amount of gas generated during the activation process is reduced by controlling the ratio of carbon monoxide and carbon dioxide to satisfy a specific range. Accordingly, the lithium secondary battery of the present invention has the advantage of not only improving safety but also easily improving the charge-discharge efficiency of the lithium secondary battery.
[0200] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art or those with ordinary knowledge in the art will understand that various modifications and changes can be made to the present invention without departing from the spirit and technical scope of the invention as described in the claims set forth below.
[0201] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.
Claims
Claim 1 A lithium secondary battery comprising an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes, and an electrolyte, wherein the positive electrode comprises a positive current collector; and a positive composite layer positioned on the positive current collector and comprising a positive active material, a positive additive represented by the following chemical formula 1, a conductive material, and a binder, wherein the content of the positive additive is 0.1 to 5 parts by weight per 100 parts by weight of the positive composite layer, and the lithium secondary battery satisfies the following chemical formula 1 at 2.0 or higher after charging to 100% SOC in an activation process under conditions of a temperature in the range of 40°C to 70°C, a voltage of 3.5 to 4.5 V, and a current of 0.1 to 0.5 C: [Chemical Formula 1]Li p Co (1-q) M 1 q In the above chemical formula 1, O4, M 1 ... is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively; [Equation 1]A LCO In / A0 formula 1, A LCO represents the amount of carbon monoxide (CO) and carbon dioxide (CO2) gas generated (ml / Ah) when the anode contains an anode additive represented by Chemical Formula 1, and A0 represents the amount of carbon monoxide (CO) and carbon dioxide (CO2) gas generated (ml / Ah) when the anode does not contain an anode additive represented by Chemical Formula 1. Claim 2 A lithium secondary battery satisfying Formula 1 with a value of 3.0 or higher in claim 1. Claim 3 In claim 1, the lithium secondary battery is a lithium secondary battery satisfying the following Equation 2 to be 0.8 or less: [Equation 2] B LCO In / B0 formula 2, B LCO represents the gas generation amount (ml / Ah) of propene (C3H6) and propane (C3H8) when the anode contains an anode additive represented by Chemical Formula 1, and B0 represents the gas generation amount (ml / Ah) of propene (C3H6) and propane (C3H8) when the anode does not contain an anode additive represented by Chemical Formula 1. Claim 4 In claim 1, the anode additive is a lithium secondary battery having a tetragonal structure with a space group of P42 / nmc. Claim 5 delete Claim 6 In claim 1, the lithium secondary battery wherein the positive active material is a lithium metal composite oxide represented by the following chemical formula 2: [Chemical Formula 2]Li x [Ni y Co z Mn w M 2 v ]O u In the above chemical formula 2, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and x, y, z, w, v, and u are 1.0≤x≤1.30, 0.1≤y<0.95, and 0.01, respectively. <z≤0.5, 0.01<w≤0.5, 0≤v≤0.2, 1.5≤u≤4.5이다. Claim 7 A lithium secondary battery according to claim 1, wherein the conductive material comprises one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Denka black, Ketjen black, Super-P, Channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes. Claim 8 A lithium secondary battery according to claim 1, wherein the conductive material is included in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the positive electrode composite layer. Claim 9 A lithium secondary battery according to claim 1, wherein the negative electrode comprises a negative electrode current collector and a negative electrode composite layer located on the negative electrode current collector and containing a negative electrode active material, and the negative electrode active material contains a carbon material and a silicon material. Claim 10 In paragraph 9, the silicon material is silicon (Si) particles and silicon oxide (SiO₂). X A lithium secondary battery containing one or more of the particles , 1≤X≤2. Claim 11 A lithium secondary battery according to claim 9, wherein the silicon material is included in an amount of 1 to 20 parts by weight in 100 parts by weight of the negative electrode composite layer. Claim 12 A method for activating a lithium secondary battery according to claim 1, comprising the process of charging the lithium secondary battery to an SOC of 10% to 100% under conditions of a temperature in the range of 40℃ to 70℃, a voltage of 3.5 to 4.5 V, and a current of 0.1 to 0.5 C.
Citation Information
Patent Citations
Lithium ion secondary battery
JP2019145402A
